Inhibiting effects of three phosphates on coal spontaneous combustion. Issue 10 (3rd October 2022) - Hou, Xinran; Guo, Liwen; Wang, Fusheng
ABSTRACT: In order to investigate P -containing flame retardant on coal spontaneous combustion, trisodium phosphate, sodium hexametaphosphate, and ammonium polyphosphate were selected. Raw coal and inhibitor solution (10 wt%) were mixed at weight ratio 4:1. Coal (raw coal, inhibited coals) oxidation reaction was measured by own designed temperature-programming device. Simultaneous TG-DSC was carried out. Evolution of CO with increasing temperature and cross point temperature (CPT) were obtained of coal oxidation reaction; these results showed that the addition of (NaPO3 )6 and ammonium polyphosphate (APP) to raw coal had an obvious suppression effect during low-temperature oxidation. CPT of APP-inhibited coal was 16°C higher than that of raw coal. TG-DTG curve results revealed that characteristic temperatures and mass fraction (ω) of APP-inhibited coal were significantly higher than other coal samples. Initial exothermal temperatures, thermal peak temperatures, and inhibition ratio were obtained from DSC curves. The results all demonstrated that APP had obvious inhibition effects on the whole coal oxidation. Infrared spectrograms of release gases showed that temperatures of the maximum release value and the whole quantity of gas products (CO2, CH4, CO, and H2 O) were decreased due to the addition of APP by eliminating free radicals and diluting the amount of oxygen in the surrounding coal sample.